Peran good corporate governance dalam pengelolaan manajemen risiko pada industri perbankan syariah - Mufayidah, Salma Nasywa (Maliki Interdisciplinary Journal, 2024)
Sharia banks must apply the principles of Good Corporate Governance to achieve company sustainability by paying attention to interested parties. One of the bank's relationships with customers is depositing money in the bank based on trust and security so every bank is required to maintain a relationship of trust and increase its security. This research is included in the qualitative research category which uses a case study approach. This research uses secondary data, which was obtained by reviewing relevant literature about the problem discussed and relevant theories. This research shows that risk management is necessary for the Islamic banking industry, which must be carried out carefully so that the Islamic banking market continues to run according to its objectives and does not harm various parties. By using the role of Good Corporate Governance, one must follow the principles of Good Corporate Governance, namely transparency, accountability, responsibility, independence as well as fairness and equality.